Does bank capital reduce liquidity creation? - Evans, Joshua; Haq, Mamiza (Elsevier, 2021)
This paper investigates the relationship between bank capital and liquidity creation against the backdrop of the 2007–2008 financial crisis. Analyzing an unbalanced panel of 11,617 U.S. commercial banks from 1996 to 2016, we find a negative association between regulatory capital and on-balance-sheet liquidity creation, but positive associations for small banks and after the financial crisis. Further, we observe lower liquidity creation among banks that participated in the Troubled Asset Relief Program (TARP). The results are largely robust to several alternate variable proxies and model specifications. Our findings suggest that “one-size-fits-all” policy may have some unintended consequences for banks.